The Study of Socioeconomic and Environmental Aspects of Dolomite Limestone Mining in Tuban Regency - Sutrisno Sutrisno; Azhari Azhari (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2020)
Limestone mining in Tuban District has serious problems due to unlicensed mining that does not comply with conservation rules and mining procedures standards. This review article aims to study the socioeconomic and environmental aspects of limestone mining in Tuban Regency. Limestone mining by the village community substantially meets the eligibility criteria. Most of them work as unlicensed or illegal miners, mining kumbung limestone as material for building bricks. They generally work for landowners or investors who have limestone management rights. Livelihoods as miners provide better welfare guarantees compared to working on agricultural land. Limestone mining activities have impacted the destruction of the natural landscape, leaving lakes, caves, or giant holes in the ex-mining limestone hills. Efforts to resolve the issue include licensing arrangements, partnerships to improve the status of illegal miners, reclamation work to control erosion, and the development of the limestone tourism business. JEL Classification: J21, L72, Q15